ANTARA KONSEP DAN REALITAS: MINIMNYA IMPLEMENTASI KURIKULUM BERBASIS CINTA DALAM PENGUATAN MODERASI BERAGAMA DI MADRASAH TSANAWIYAH PALEMBANG - Rahmawati; Ahmad Zainuri; Muslim Gani Yasir (STKIP Subang, 2026)
The Love-Based Curriculum (LBC) is an educational innovation initiated by the Ministry of Religious Affairs as a response to the increasing issues of intolerance, radicalism, and moral degradation among students. However, the implementation of LBC in madrasahs, particularly in Palembang, remains limited and uneven. This study aims to analyze the role of the Love-Based Curriculum in fostering religious moderation in Madrasah Tsanawiyah in Palembang. The research employs a qualitative approach through literature review and conceptual analysis. The findings indicate that LBC plays a significant role in instilling values of tolerance, empathy, and inclusiveness. Nevertheless, the number of madrasahs that have implemented LBC is still very limited. Therefore, strengthening policy support and enhancing teachers’ capacity are necessary to expand the implementation of LBC.